The effect of heavy metals on biodegradation of carbofuran by microbial strain enriched from Agricultural areas - Mustapha, Mohammed Umar; Halimoon, Normala (African Science Publications, 2022)
The effect of heavy metals on the degradation of carbofuran by immobilzed bacterial cell was checked by culturing in the MSM medium at 37oC in the presence of 0-1 mg/L of heavy metals. Bioremediation systems represent a biologically sustainable means to degrading organic pollutants such as carbofuran insecticide, with little energy demand and operational expenses in addition to high efficiency and substrate specificity. Nonetheless, heavy metals present in the agricultural lands may thwart the process efficiency by poisoning carbofuran-degrading microbial isolates. Here, we experimentally tested the tolerance of carbofuran-degrading immobilized bacterial isolated from vegetable plantation area for mercury (Hg) and copper (Cu). The of the tested metals inhibited carbofuran biodegradation to different extents, depending on concentration. At pH of 7.0 and 37°C, complete inhibition of carbofuran biodegradation by Hg occurred 0.4, 0.5, 0.6 and 0.7 mg/L, respectively. Lower concentrations of these metals decreased the rate of carbofuran− biodegradation, with relatively long lag times. Interestingly, the immobilize isolate tolerated higher concentrations, although both the rate and extent of carbofuran− biodegradation were affected.